COVID-19 PERITRAUMATIC DISTRESS INDEX EXPLORATORY FACTOR ANALYSIS RESULTS USING A BRAZILIAN SAMPLE - Abad, Alberto (2022)
We conducted an exploratory factor analysis (EFA) to empirically derive the COVID-19 Peritraumatic Distress Index (CPDI) factor structure. Data (peri-traumatic stress during the COVID-19). We used data from the Physical and Psychological Reactions as Health Indicators Research (Virtual Laboratory of Affective, Cognitive and Behavioral Neuropsychometry – LAVINACC). EFA was implemented using a Polychoric Matrix and Robust Diagonally Weighted Least Squares (RDWLS) extraction method. We used the Parallel Analysis with random permutation, and as a rotation technique, we used the Robust Promin. The adequacy of the model was evaluated using the Root Mean Square Error of Approximation (RMSEA), Tucker-Lewis Index (TLI), and Comparative Fit Index (CFI) fit indices. The Ratio Communality Index (RCI) reported (RCI = 0.998452) showed both subsamples have a similar amount of common variance. Results showed adequacy of the polychoric correlation matrix measured by Bartlett's sphericity (21116.6, (df =   276; p < 0.00001) and KMO = 0.939. The overall assessment (UniCo = 0.918; ECV = 0.85), MIREAL = 0.200), suggested that CPDI can be treated as a two-factor structure: first factor (internal stressors), second factor (external stressors). Replication studies to verify further validity and reliability should be undertaken.